Abraham's Legacy: Togetherness of Christian and Islamic Faith - Bobby Kurnia Putrawan; Edward Everson Hanock (Jurnal Theologia, 2022)
This article is a study about Abraham, known as the ancestor obtained by Isaac and Ishmael. His offspring are already widespread. With all the inheritance given to them, get Abraham to start life in a different land and with different blessings. Here is the crucial point. The difference seems to have proved the fact that as a result of Abraham coming from fellowship and brotherhood remain intertwined and maintained, because these two things are also Abraham's legacy. Through literature studies, some data about Abraham are described in a narrative manner with the aim of being based on Abraham's inheritance, namely blessings, descent and land implemented correctly and proportionally. What is presented in this review article on two dimensions of inheritance: spiritual and community. Spiritual, from a biblical perspective, speaks of a promise, while the community is more towards the vision of sociology and managerial pluralism